Strategi Pemenangan Partai Demokrasi Indonesia Perjuangan pada Pemilu Tahun 2019 di Kabupaten Aceh Tengah - Nofriadi Nofriadi; Effendi Hasan; Ubaidullah Ubaidullah; Helmi Helmi (Jurnal Public Policy, 2021)
A political party is a political organization that adheres to and is based on a certain ideology or can also be interpreted as an organization that accommodates the interests and voices of the people who want their interests to be heard by the authorities. Political marketing and political strategy are the most important part of selling and getting a positive response from the community so that people support certain parties or certain candidates. The research method with a qualitative approach, this strategy or method of winning has been thought out and also planned long before the election day arrives, but this strategy is also inseparable from the cooperation and contribution of the political parties it carries in achieving common goals. there are several ways and strategies carried out by the PDI-P party in the 2019-2024 period and it became one of the extraordinary events so that the PDI-P party won with the most votes. The strategy carried out by the PDI-P party in Central Aceh Regency is the collaboration between legislative candidates and the community. Cooperation carried out by the PDI-P party legislative candidates is one very good way to do it, so that work plans through the voice of the community can be carried out easily because of this collaboration. The next strategy is to improve good communication with the community, increase socialization, and have a competition event held by the PDI-P party to the community. With the competition event held by the PDI-P party legislative candidates to the community, so that people know more about the nature, character, behavior and know more about who the legislative candidates are. As well as improving the system and the way the PDI-P party's legislative candidates campaign openly and privately